Family involvement and firm performance: Evidence from UK listed firms - Poutziouris, Panikkos Zata; Savva, Christos S.; Hadjielias, Elias (My University, 2015)
This study examines how family involvement affects the performance of UK companies listed on the London Stock Exchange (LSE). Using a panel dataset from 1998 to 2008, the econometric models evaluate the effect of family involvement in terms of ownership and management on firm performance (measured with accounting ratios and Tobin's Q) while controlling for a number of conditions external to the firm as well as business characteristics. Our findings illustrate a non-linear relationship between family ownership and firm performance, with performance increasing until family shareholding reaches thirty-one percent, at which point performance begins to decrease. Moreover, the findings illustrate that the higher the involvement of the family in terms of management (i.e., through a family CEO) and governance (board representation and/or CEO-Chairman dual role), the higher the performance the firm appears to sustain over the long run and across generations.
Keywords: CEO duality; Family firms; Ownership; Performance